Monitoring Soil Moisture in Chili Plants on a Household Scale Based on the Internet of Things (IoT) Using NodeMCU ESP2866 and Soil Moisture - Tiara Elmanda; Ansar Rizal; Hari Purwadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study designs and implements a soil moisture monitoring system for household-scale chili plants based on the Internet of Things (IoT) using NodeMCU ESP8266 and soil moisture sensors . The system was developed to assist users in monitoring soil moisture conditions accurately to support more efficient chili plant care. The soil moisture sensor is used to detect soil moisture levels, then the data is processed by NodeMCU ESP8266 and sent via a Wi-Fi network to the IoT platform so that it can be monitored in real-time . System testing was carried out on chili plants planted in pots by observing the sensor reading response in various soil conditions. The test results showed that the system was able to monitor changes in soil moisture stably and display information with a good response. The implementation of this system on a household scale is considered effective in assisting plant watering decisions and reducing the risk of water shortages or excesses. The designed system has the potential to be further developed by adding automatic control features and cloud- based data storage to support the implementation of sustainable smart agriculture.